Solid electrode for solid-state lithium battery and preparation method of solid electrode

By using strontium cerium co-doped lithium titanate and modified graphite as solid-state lithium battery electrode materials, the problem of unsatisfactory circulation life in the prior art is solved, and a solid-state lithium battery electrode with high cycle stability and long life is achieved.

CN119833552APending Publication Date: 2025-04-15CHANGZHOU YISULFUR BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022011.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The circulation life of existing solid-state lithium batteries is not ideal and it is difficult to meet the practical application needs.

Method used

Strontium cerium co-doped lithium titanate and modified graphite are used as electrode materials for solid-state lithium batteries, and are prepared by ultrasonic dispersion, calcination treatment and hot pressing to improve the cyclic stability of the electrode.

Benefits of technology

1000 cycles at 10C ratio, the capacity retention rate can reach 91.5%, significantly improving the circulation life of solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231655610000131
    Figure BDA0005231655610000131
Patent Text Reader

Abstract

The invention relates to the technical field of solid batteries, and discloses a solid electrode for a solid-state lithium battery and a preparation method of the solid electrode. The solid electrode for the solid-state lithium battery comprises the following raw materials in parts by mass: 5-10 parts of strontium-cerium co-doped lithium titanate and 2-3 parts of modified graphite. The solid electrode for the solid-state lithium battery provided by the invention is circulated for 1000 times at 10C multiplying power, the capacity retention ratio can reach 91.5%, and the solid electrode has relatively long cycle service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid batteries, and in particular to a solid electrode for a solid lithium battery and a preparation method thereof. Background Art

[0002] Solid-state batteries are batteries that use solid electrodes and solid electrolytes. Compared with the widely used organic electrolyte lithium-ion batteries, solid-state batteries do not contain liquid electrolytes, thus avoiding the occurrence of leakage and other problems, making solid-state batteries safer. In addition, the core advantage of solid-state batteries lies in their high energy density, which can theoretically reach 400Wh / kg. Moreover, solid-state batteries are stable under high temperature conditions, are not prone to thermal runaway, and the risk of spontaneous combustion and explosion is greatly reduced. Therefore, solid-state batteries have become an ideal object for the next generation of new energy vehicle power batteries.

[0003] Some existing solid-state battery electrode materials often use lithium-ion electrodes as anode materials. This is because lithium ions can combine with solid electrolyte materials to form lithium-ion transmission channels, thereby making solid-state batteries have higher energy density, longer service life and better safety; however, in actual applications, people have found that when using existing lithium-ion electrodes as anode materials, the cycle life of the battery is not ideal. Therefore, providing a lithium-ion solid electrode with a higher cycle life has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention

[0004] The purpose of the present invention is to provide a solid electrode for a solid-state lithium battery and a preparation method thereof, wherein the solid electrode for a solid-state lithium battery has a high cycle life.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A solid electrode for a solid lithium battery comprises the following raw materials in parts by mass: 5 to 10 parts of strontium-cerium co-doped lithium titanate and 2 to 3 parts of modified graphite.

[0008] Furthermore, the preparation method of the strontium-cerium co-doped lithium titanate comprises the following steps:

[0009] 1) adding strontium chloride and cerium chloride into water to obtain a mixed solution;

[0010] 2) adding lithium titanate to the mixed solution prepared in step 1), dispersing by ultrasonication, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0011] 3) calcining the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) to obtain the strontium-cerium co-doped lithium titanate.

[0012] Furthermore, in step 1), the mass volume ratio of strontium chloride, cerium chloride and water is 1 g: (0.8-1.2) g: (40-60) mL.

[0013] Furthermore, in step 2), the mass volume ratio of the lithium titanate and the mixed solution is 100 g: (40-60) mL.

[0014] Furthermore, in step 2), the duration of the ultrasonic dispersion is 2 hours.

[0015] Furthermore, in step 3), the calcination treatment is specifically: placing the lithium titanate adsorbed with strontium chloride and cerium chloride in an air atmosphere, and calcining it at 900-1000° C. for 30 minutes.

[0016] Furthermore, the preparation method of the modified graphite comprises the following steps:

[0017] 1) calcining and modifying graphite to obtain calcined modified graphite;

[0018] 2) placing the calcined modified graphite prepared in step 1) in a mixed solution consisting of a hydrochloric acid solution and a citric acid solution for immersion modification to obtain acid-modified graphite, namely the modified graphite.

[0019] Furthermore, in step 1), the calcination modification is specifically: placing the graphite in a nitrogen atmosphere, preheating at 100° C. for 20 minutes, and then calcining and modifying it at 160-200° C. for 1 hour.

[0020] Furthermore, in step 2), the concentration of the hydrochloric acid solution is 0.1 mol·L -1 .

[0021] Furthermore, in step 2), the concentration of the citric acid solution is 0.6 mol·L -1 .

[0022] Furthermore, in step 2), the mass volume ratio of the calcined modified graphite, the hydrochloric acid solution and the citric acid solution is (3-5) g: (6-10) mL: (3-5) mL.

[0023] Furthermore, in step 2), the impregnation modification is specifically: impregnation modification at 50° C. for 30 to 60 minutes.

[0024] Furthermore, in step 2), after the impregnation modification is completed, the calcined modified graphite needs to be placed in a nitrogen atmosphere and heated at 80° C. for 5 minutes to remove excess acid on the surface of the calcined modified graphite.

[0025] The second technical solution of the present invention:

[0026] The method for preparing the solid electrode for the solid-state lithium battery comprises the following steps:

[0027] The strontium-cerium co-doped lithium titanate and modified graphite are mixed, ball-milled, and hot-pressed to obtain the solid electrode for the solid-state lithium battery.

[0028] Furthermore, the ball milling time is 1 hour.

[0029] Furthermore, the hot pressing is specifically: hot pressing at 100° C. and 5 MPa for 30 minutes.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] A solid electrode for a solid-state lithium battery provided by the present invention can be cycled 1000 times at a rate of 10C, and the capacity retention rate can reach 91.5%, thereby having a relatively high cycle life. DETAILED DESCRIPTION

[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] In the following examples and comparative examples, unless otherwise specified, all raw materials used are commercially available.

[0038] In the following embodiments, a method for preparing a solid electrode for a solid-state lithium battery comprises the following steps:

[0039] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0040] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g: (0.8-1.2) g: (40-60) mL to obtain a mixed solution;

[0041] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g: (40-60) mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0042] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 900-1000° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0043] 2. Preparation of modified graphite:

[0044] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 160-200° C. for 1 h to obtain calcined modified graphite;

[0045] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of (3-5) g: (6-10) mL: (3-5) mL, the calcined modified graphite prepared in step 1) is placed in a 0.1 mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 30 to 60 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0046] 3. Preparation of solid electrode:

[0047] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being (5-10): (2-3), the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0048] Example 1

[0049] A solid electrode for solid-state lithium battery

[0050] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0051] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:0.8 g:40 mL to obtain a mixed solution;

[0052] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:40 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0053] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 900° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0054] 2. Preparation of modified graphite:

[0055] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 160° C. for 1 h to obtain calcined modified graphite;

[0056] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of 3g:6mL:3mL, the calcined modified graphite prepared in step 1) was placed in a 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 30 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e., modified graphite;

[0057] 3. Preparation of solid electrode:

[0058] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 5:2, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0059] Example 2

[0060] A solid electrode for solid-state lithium battery

[0061] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0062] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:1 g:50 mL to obtain a mixed solution;

[0063] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0064] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0065] 2. Preparation of modified graphite:

[0066] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 180° C. for 1 h to obtain calcined modified graphite;

[0067] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of 4g:8mL:4mL, the calcined modified graphite prepared in step 1) was placed in a 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 40 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0068] 3. Preparation of solid electrode:

[0069] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 8:2.5, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0070] Example 3

[0071] A solid electrode for solid-state lithium battery

[0072] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0073] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:1.2 g:60 mL to obtain a mixed solution;

[0074] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:60 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0075] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 1000° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0076] 2. Preparation of modified graphite:

[0077] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 200° C. for 1 h to obtain calcined modified graphite;

[0078] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of 5g:10mL:5mL, the calcined modified graphite prepared in step 1) was placed in a 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 60 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0079] 3. Preparation of solid electrode:

[0080] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 10:3, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0081] Comparative Example 1

[0082] A solid electrode for solid-state lithium battery

[0083] 1. Preparation of strontium-doped lithium titanate:

[0084] 1) adding strontium chloride to water in a mass volume ratio of strontium chloride to water of 2 g:50 mL to obtain a strontium chloride solution;

[0085] 2) adding lithium titanate to the strontium chloride solution prepared in step 1) at a mass volume ratio of lithium titanate to strontium chloride solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride;

[0086] 3) placing the lithium titanate adsorbed with strontium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain strontium-doped lithium titanate;

[0087] 2. Preparation of modified graphite:

[0088] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 180° C. for 1 h to obtain calcined modified graphite;

[0089] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of 4g:8mL:4mL, the calcined modified graphite prepared in step 1) was placed in a 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 40 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0090] 3. Preparation of solid electrode:

[0091] According to the mass ratio of strontium-doped lithium titanate to modified graphite of 8:2.5, the strontium-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0092] Comparative Example 2

[0093] A solid electrode for solid-state lithium battery

[0094] 1. Preparation of cerium-doped lithium titanate:

[0095] 1) adding cerium chloride to water in a mass volume ratio of cerium chloride to water of 2 g:50 mL to obtain a cerium chloride solution;

[0096] 2) adding lithium titanate to the cerium chloride solution prepared in step 1) in a mass volume ratio of lithium titanate to cerium chloride solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with cerium chloride;

[0097] 3) placing the lithium titanate adsorbed with cerium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain cerium-doped lithium titanate;

[0098] 2. Preparation of modified graphite:

[0099] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 180° C. for 1 h to obtain calcined modified graphite;

[0100] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of 4g:8mL:4mL, the calcined modified graphite prepared in step 1) was placed in a 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 40 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0101] 3. Preparation of solid electrode:

[0102] According to the mass ratio of cerium-doped lithium titanate to modified graphite of 8:2.5, the cerium-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0103] Comparative Example 3

[0104] A solid electrode for solid-state lithium battery

[0105] 1. Preparation of modified graphite:

[0106] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 180° C. for 1 h to obtain calcined modified graphite;

[0107] 2) According to the mass volume ratio of calcined modified graphite, hydrochloric acid solution and citric acid solution of 4g:8mL:4mL, the calcined modified graphite prepared in step 1) was placed in a 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 40 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0108] 2. Preparation of solid electrode:

[0109] According to the mass ratio of lithium titanate to modified graphite of 8:2.5, lithium titanate and the modified graphite prepared in step 1 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0110] Comparative Example 4

[0111] A solid electrode for solid-state lithium battery

[0112] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0113] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:1 g:50 mL to obtain a mixed solution;

[0114] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0115] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0116] 2. Preparation of modified graphite:

[0117] According to the mass volume ratio of graphite, hydrochloric acid solution and citric acid solution of 4g:8mL:4mL, graphite was placed in a solution with a concentration of 0.1mol·L -1 The hydrochloric acid solution and the concentration are 0.6mol·L -1 The calcined modified graphite is immersed in a mixed solution consisting of a citric acid solution at 50°C for 40 minutes, and then the calcined modified graphite is placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0118] 3. Preparation of solid electrode:

[0119] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 8:2.5, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0120] Comparative Example 5

[0121] A solid electrode for solid-state lithium battery

[0122] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0123] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:1 g:50 mL to obtain a mixed solution;

[0124] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0125] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0126] 2. Preparation of modified graphite:

[0127] The graphite is placed in a nitrogen atmosphere, preheated at 100°C for 20 minutes, and then calcined and modified at 180°C for 1 hour to obtain calcined modified graphite, i.e. modified graphite;

[0128] 3. Preparation of solid electrode:

[0129] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 8:2.5, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0130] Comparative Example 6

[0131] A solid electrode for solid-state lithium battery

[0132] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0133] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:1 g:50 mL to obtain a mixed solution;

[0134] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0135] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0136] 2. Preparation of modified graphite:

[0137] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 180° C. for 1 h to obtain calcined modified graphite;

[0138] 2) According to the mass volume ratio of calcined modified graphite and citric acid solution of 4g:4mL, the calcined modified graphite prepared in step 1) is placed in a citric acid solution with a concentration of 0.6mol·L -1 The calcined modified graphite was immersed in a citric acid solution at 50°C for 40 minutes, and then the calcined modified graphite was placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0139] 3. Preparation of solid electrode:

[0140] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 8:2.5, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0141] Comparative Example 7

[0142] A solid electrode for solid-state lithium battery

[0143] 1. Preparation of strontium-cerium co-doped lithium titanate:

[0144] 1) adding strontium chloride and cerium chloride into water in a mass volume ratio of strontium chloride, cerium chloride and water of 1 g:1 g:50 mL to obtain a mixed solution;

[0145] 2) adding lithium titanate to the mixed solution prepared in step 1) according to the mass volume ratio of lithium titanate to the mixed solution of 100 g:50 mL, ultrasonically dispersing for 2 h, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride;

[0146] 3) placing the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) in an air atmosphere, and calcining at 950° C. for 30 min to obtain strontium-cerium co-doped lithium titanate;

[0147] 2. Preparation of modified graphite:

[0148] 1) placing graphite in a nitrogen atmosphere, preheating at 100° C. for 20 min, and then calcining and modifying at 180° C. for 1 h to obtain calcined modified graphite;

[0149] 2) According to the mass volume ratio of calcined modified graphite and hydrochloric acid solution of 4g:8mL, the calcined modified graphite prepared in step 1) is placed in a solution with a concentration of 0.1mol·L -1The calcined modified graphite was immersed in a hydrochloric acid solution at 50°C for 40 minutes, and then the calcined modified graphite was placed in a nitrogen atmosphere and heated at 80°C for 5 minutes to remove excess acid on the surface of the calcined modified graphite to obtain acid-modified graphite, i.e. modified graphite;

[0150] 3. Preparation of solid electrode:

[0151] According to the mass ratio of strontium cerium co-doped lithium titanate and modified graphite being 8:2.5, the strontium cerium co-doped lithium titanate prepared in step 1 and the modified graphite prepared in step 2 are mixed, ball-milled for 1 hour, and then hot-pressed at 100° C. and 5 MPa for 30 minutes to obtain the solid electrode for the solid-state lithium battery.

[0152] The solid electrodes for solid-state lithium batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were subjected to a cycle stability test (1000 cycles at a rate of 10C, for details, see "One-step preparation of lithium titanate composite electrodes and research on their performance" by Dong Hao et al.), and the cycle stability test results are shown in Table 1;

[0153] Table 1 Cyclic stability test results

[0154]

[0155] It can be seen from the data in Table 1 that a solid electrode for a solid-state lithium battery provided by the present invention can maintain a capacity of 91.5% after 1000 cycles at a rate of 10C, and has a relatively high cycle life; while omitting the doping of strontium and / or cerium in lithium titanate, omitting the calcination modification of graphite, omitting the acid modification of graphite, and omitting the addition of hydrochloric acid solution or citric acid solution in the acid modification of graphite will reduce the cycle life of the solid electrode for a solid-state lithium battery to a certain extent.

[0156] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A solid electrode for a solid-state lithium battery, characterized in that: The invention comprises the following raw materials in parts by weight: 5 to 10 parts of strontium-cerium co-doped lithium titanate and 2 to 3 parts of modified graphite.

2. A solid electrode for a solid-state lithium battery according to claim 1, characterized in that: The preparation method of strontium-cerium co-doped lithium titanate comprises the following steps: 1) adding strontium chloride and cerium chloride into water to obtain a mixed solution; 2) adding lithium titanate to the mixed solution prepared in step 1), dispersing by ultrasonication, and drying to obtain lithium titanate adsorbed with strontium chloride and cerium chloride; 3) calcining the lithium titanate adsorbed with strontium chloride and cerium chloride obtained in step 2) to obtain the strontium-cerium co-doped lithium titanate.

3. A solid electrode for a solid-state lithium battery according to claim 2, characterized in that: In step 1), the mass volume ratio of strontium chloride, cerium chloride and water is 1 g: (0.8-1.2) g: (40-60) mL.

4. A solid electrode for a solid-state lithium battery according to claim 2, characterized in that: In step 2), the mass volume ratio of the lithium titanate and the mixed solution is 100 g: (40-60) mL; and the duration of the ultrasonic dispersion is 2 h.

5. A solid electrode for a solid-state lithium battery according to claim 2, characterized in that: In step 3), the calcination treatment is specifically: placing the lithium titanate adsorbed with strontium chloride and cerium chloride in an air atmosphere, and calcining it at 900-1000° C. for 30 minutes.

6. A solid electrode for a solid-state lithium battery according to claim 1, characterized in that: The preparation method of the modified graphite comprises the following steps: 1) calcining and modifying graphite to obtain calcined modified graphite; 2) placing the calcined modified graphite prepared in step 1) in a mixed solution consisting of a hydrochloric acid solution and a citric acid solution for immersion modification to obtain acid-modified graphite, namely the modified graphite.

7. A solid electrode for a solid-state lithium battery according to claim 6, characterized in that: In step 1), the calcination modification is specifically as follows: placing the graphite in a nitrogen atmosphere, preheating at 100° C. for 20 minutes, and then calcining and modifying at 160-200° C. for 1 hour.

8. A solid electrode for a solid-state lithium battery according to claim 6, characterized in that: In step 2), the concentration of the hydrochloric acid solution is 0.1 mol·L -1 ; The concentration of the citric acid solution is 0.6 mol·L -1 ; The mass volume ratio of the calcined modified graphite, hydrochloric acid solution and citric acid solution is (3-5) g: (6-10) mL: (3-5) mL; the impregnation modification is specifically: impregnation modification at 50°C for 30-60 minutes.

9. A method for preparing a solid electrode for a solid-state lithium battery as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: The strontium-cerium co-doped lithium titanate and modified graphite are mixed, ball-milled, and hot-pressed to obtain the solid electrode for the solid-state lithium battery.

10. The preparation method according to claim 9, characterized in that: The ball milling time is 1 hour; the hot pressing is specifically: hot pressing at 100° C. and 5 MPa for 30 minutes.